The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/bit.27938
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas putida KT2440 endures temporary oxygen limitations

Abstract: The obligate aerobic nature of Pseudomonas putida, one of the most prominent whole-cell biocatalysts emerging for industrial bioprocesses, questions its ability to be cultivated in large-scale bioreactors, which exhibit zones of low dissolved oxygen tension. P. putida KT2440 was repeatedly subjected to temporary oxygen limitations in scale-down approaches to assess the effect on growth and an exemplary production of rhamnolipids. At those conditions, the growth and production of P. putida KT2440 were decelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…P. putida KT2440 SK4 with attTn7::Pffg-rhlAB [23,24], is a RL-producing whole-cell biocatalyst, which tolerates temporary oxygen depletion [22]. Its chassis strain, P. putida KT2440 [26][27][28], is classified as host-vector system with safety level 1 (HV1).…”
Section: Bacterial Strain and Cultivation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P. putida KT2440 SK4 with attTn7::Pffg-rhlAB [23,24], is a RL-producing whole-cell biocatalyst, which tolerates temporary oxygen depletion [22]. Its chassis strain, P. putida KT2440 [26][27][28], is classified as host-vector system with safety level 1 (HV1).…”
Section: Bacterial Strain and Cultivation Methodsmentioning
confidence: 99%
“…Additionally, cell retention, commonly applied for in situ liquid-liquid extraction with an external loop to prevent the organisms from excessive anaerobic residence times, is not required [21]. Regarding anaerobe residence times in the MPLR, we previously showed that a short-term oxygen limitation, the obligate aerobe organism P. putida might be exposed to in the MPLR, only influences the productivity due to moderately slower growth and production while the final biomass and product titers remain unaltered [22].…”
Section: Introductionmentioning
confidence: 99%
“…P. putida KT2440 is a known obligate aerobe, and cannot use alternative terminal electron acceptors during oxidative phosphorylation (30). Because of this, oxidized nitrogen species can only be used as nitrogen sources.…”
Section: Inorganic Nitrogen Sources and Ureamentioning
confidence: 99%
“…In P. aeruginosa, a bacterium with clinical importance, the regulatory sRNA PhrS is induced to thrive under anaerobiosis and its transcription is activated by Anr, the oxygen responsive regulator homologue of the FNR protein of E. coli (Hoe et al, 2013). Pseudomonas aeruginosa's sRNAs are the most studied within the genus G omez-Lozano et al, 2014;Miller et al, 2016;Taylor et al, 2017); however, metabolic variability under different oxygen availability conditions can be found among Pseudomonas species (Arai, 2011;Tribelli et al, 2019;Demling et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…coli (Hoe et al ., 2013). Pseudomonas aeruginosa's sRNAs are the most studied within the genus (Sonnleitner et al ., 2011; Gómez‐Lozano et al ., 2014; Miller et al ., 2016; Taylor et al ., 2017); however, metabolic variability under different oxygen availability conditions can be found among Pseudomonas species (Arai, 2011; Tribelli et al ., 2019; Demling et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%